IDENTIFIKASI MISKONSEPSI MATERI MEKANIKA DENGAN MENGGUNAKAN CRI (CERTAINTY OF RESPONSE INDEX) - VENNY HARIS (Ta'dib, 2013)
It has been done a descriptive quantitative research about The identification of mechanical Misconception Concept by Using CRI (Certainty of Response Index). This research was applied to the first semester students of Physical Science Department of STAIN Batusangkar who were registered in 2011/2012 academic year that consisted of 55 students. In collecting the data, the instrument of this research was test in multiple choice form. It consisted 30 items. In asnwering the question, the students were asked to write CRI mark (0-5) as level of their believe to their answer. A misconception student can be known by comparing his or her answer based on CRI s/he fills. Research result showed that 80 % students did misconception of the time concept of free falling bodies, 45 % students did not know the concept of action (aksi) and reaction (reaksi), and 7.27 % students knew the concept of Newton Formula 1. It can be concluded that the level of misconception of the first semester students of Physical Science Department of STAIN Batusangkar who were registered in 2011/2012 academic year was very high.Kata kunci: miskonsepsi fisika, instrumen, mekanika, CRI (Certainty of Response Index)